Inception cohort of the Swiss Spinal Cord Injury Cohort Study (SwiSCI): Design, participant characteristics, response rates and non-response - Fekete, C; Gurtner, B; Kunz, S; Gemperli, A; Gmünder, H; Hund-Georgiadis, M; Jordan, X; Schubert, M; Stoyanov, J; Stucki, G (Journal of rehabilitation medicine, 2021)
To provide a methodological reference paper for the inception cohort of the Swiss Spinal Cord Injury Cohort Study (SwiSCI), by detailing its methodological features and reporting on participant characteristics, response rates and non-response bias. Prospective cohort study starting in 2013 in all 4 specialized rehabilitation centres in Switzerland. Included are 655 newly diagnosed first rehabilitation patients aged ≥16 years with traumatic or non-traumatic spinal cord injury (TSCI, NTSCI). Descriptive statistics were used to depict participant characteristics and to compare characteristics of responders and non-responders. Logistic regressions were conducted to estimate non-response bias. The sample consisted of 69% males, with mean age 53.5 years, 57.9% TSCI, 60.7% paraplegia and 78.8% incomplete SCI. Males and younger persons more often sustained TSCI and more severe SCI, resulting in longer duration of rehabilitation. Complete lesions were more prevalent in TSCI compared to NTSCI. The response rate was 47.5% and study participation was less likely in females, older persons, persons with lower functional independence and those with NTSCI. SwiSCI inception cohort data enable the estimation of epidemiological figures of SCI in Switzerland, and prognostic and trajectory modelling of outcomes after SCI to guide policy, service provision and clinical practice.